Studies of human pancreatic elastase treatment of rabbit and human vein rings to predict human therapeutic doses. Issue 3 (2nd April 2016) - Burke, Steven K.; Bunton, David; Bingham, Karen; Moss, Emma; Bland, Kimberly S.; Starcher, Barry; Wong, Marco D.; Franano, F. Nicholas
Abstract: Vascular tissue contains abundant elastic fibers that contribute to vessel elasticity. Vonapanitase (formerly PRT‐201) is a recombinant human chymotrypsin‐like elastase family member 1 (CELA1) shown to cleave the elastin component of elastic fibers, resulting in increased vessel diameter. The purpose of these current studies was to determine vein diameter, wall thickness, elastin content, and vonapanitase potency in veins used in a model of arteriovenous fistula (AVF) and in patients undergoing AVF creation for hemodialysis access to guide dose selection for human trials. Rabbit linguofacial, maxillary, and external jugular veins, and human basilic and upper and lower arm cephalic veins were dissected postmortem and sectioned into 2 mm length rings. Rings were incubated in vonapanitase at 37°C at varying concentrations and times. Elastin content was estimated histologically and by quantifying desmosine, a protein cross‐link unique to elastin. Rabbit veins were substantially thinner and contained less elastin than human veins. In human veins, elastin content was greatest in basilic and least in lower arm cephalic. Vonapanitase removed elastin in a time‐ and concentration‐dependent manner in all vein types. A lower concentration of vonapanitase was required to remove elastin from rabbit relative to human veins. In summary, vonapanitase reduced the elastin content of rabbit and human veins but did so at a lower concentration in the rabbit veins. Rabbit models may overestimate the potency of vonapanitase in humans. These results indicate that human dose selection should be guided by human vein ring experiments.